2023
DOI: 10.1111/1755-0998.13897
|View full text |Cite
|
Sign up to set email alerts
|

How do threatened plant species with low genetic diversity respond to environmental stress? Insights from comparative conservation epigenomics and phenotypic plasticity

Brigette R. Williams,
Allison J. Miller,
Christine E. Edwards

Abstract: Many threatened plants have low genetic diversity, which may reduce their capacity for genetically based adaptation, increasing their extinction risk. Non‐genetic variation (e.g. epigenomic modifications such as DNA methylation) and plasticity may facilitate the persistence of threatened plants, yet are rarely incorporated into conservation assessments. We present a case study investigating variation and plasticity in DNA methylation and phenotypic traits in four genetically depauperate species ofLeavenworthia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 91 publications
1
2
0
Order By: Relevance
“…In this study, we found absence of correlation between genetic and epigenetic distances across individuals in the two study species, supporting it would be worth to experimentally exploring their relative contribution to individual phenotypes and their plasticities under controlled environmental conditions (see e.g. Williams et al, 2023).…”
Section: Genetic and Methylation Variation In Natural Populations Of ...supporting
confidence: 51%
See 2 more Smart Citations
“…In this study, we found absence of correlation between genetic and epigenetic distances across individuals in the two study species, supporting it would be worth to experimentally exploring their relative contribution to individual phenotypes and their plasticities under controlled environmental conditions (see e.g. Williams et al, 2023).…”
Section: Genetic and Methylation Variation In Natural Populations Of ...supporting
confidence: 51%
“…Understanding the sources of natural phenotypic variation is a crucial question in ecology and evolution. The idea that epigenetic diversity can compensate for reduced genetic diversity, promoting phenotypic variation through trait plasticity in response to environmental changes is relatively new (Balao et al, 2018; Bossdorf et al 2008; Richards et al, 2017; Richards, 2006; Williams et al, 2023). Trait plasticity can be particularly advantageous for sessile organisms such as plants, with limited escape strategies to face environmental perturbations and, thus, the magnitude and population structure of genetic and epigenetic diversities in plant species with disparate genomic and ecological features warrants comprehensive investigation (Anderson & Gezon, 2015; Herrera et al,2022; Richards et al, 2017; Szukala et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation